The role of the gut microbiota in childhood obesity - Bała, Kamila; Staszko , Natalia (Quality in Sport, 2026)
The gut microbiota has emerged as an important factor influencing metabolic health of people. Recent research indicates that children with obesity present distinct microbial compositions compared with their normal-weight peers, suggesting a potential role of intestinal microorganisms in the development adiposity. This paper discusses current findings on how dietary patterns, perinatal exposures and inherited microbial traits shape the gut microbiome in childhood. Particular attention is given to taxa associated with metabolic alterations, as well as to microbial metabolites that may influence energy balance and inflammation. Studies linking the gut microbiota to anthropometric measures and early markers of cardiovascular dysfunction highlight its potential value as a diagnostic tool. Understanding these complex host–microbe interactions may contribute to the development of targeted microbiota-based interventions and personalized therapeutic strategies aimed at preventing or treating childhood obesity.